Efektivitas Model Game Based Learning Berbantuan Media Wordwall pada Materi Keragaman Budaya dan Kearifan Lokal Terhadap Hasil Belajar Siswa Kelas IV SD Negeri 1 Gandasoli - Haetin, Nonoh; Falah, Irfan Fajrul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of the Game Based Learning model assisted by Wordwall media on the topic of cultural diversity and local wisdom in improving the learning outcomes IV students at SD Negeri 1 Gandasoli. The research method used was quantitative with a experimental non-equivalent control group design. The subjects of this study were 21 students from class IV-A. The instrument used was a multiple-choice test to measure students’learning outcomes before and after the implementation of the learning model. The data analysis results showed an increase in the average learning outcomes after the application of the Games Based Learning model using wordwall media. Data were analyzed descriptively quantitatively. The results of the paired sample t-test showed a t-count value of -11,266, which was greater than the t-table value of 2,086, with a significance value of 0,000 < 0,05. This indicates a significant difference between the learning outcomes before and after the treatment. Therefore, it can be concluded that the Game Based Learning model assisted by wordwall media is effective in improving students’ learning outcomes in the topic of cultural diversity and local wisdom. This media can serve as an alternative interactive learning tool to create a fun and meaningful learning atmosphere.